Paphiopedilum erythroanthum, a new species of slipper orchid (Cypripedioideae, Orchidaceae) from China based on morphological and molecular data - Liao, Xing-Yu; Zhang, Di-Yang; Lan, Si-Ren; Liu, Zhong-Jian (Phytotaxa, 2019)
A new species of Paphiopedilum (Orchidaceae) from Yunnan, China is described and illustrated based on examining morphological and molecular evidence. Morphological comparisons indicate that the new species P. erythroanthum is somewhat similar to P. henryanum, from which it differs by its shorter scape, larger and purple-red flower without purple spots, an obovate dorsal sepal, narrowly oblong petals with recurved apex and a cordate staminode. Molecular analyses of combined nuclear and plastid datasets (ITS and matK) indicate that P. erythroanthum is sister to P. notatisepalum, which has leaves with large yellow spots, a shorter scape, larger flower, white sepals and petals with large purple spots. The morphological and molecular evidence support the hypothesis that P. erythroanthum is a new species.